1999
DOI: 10.1001/jama.281.4.335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lifestyle Activity vs Structured Aerobic Exercise in Obese Women<SUBTITLE>A Randomized Trial</SUBTITLE>

Abstract: A program of diet plus lifestyle activity may offer similar health benefits and be a suitable alternative to diet plus structured aerobic activity for obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
299
0
22

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 578 publications
(336 citation statements)
references
References 14 publications
15
299
0
22
Order By: Relevance
“…23,24 However, exercise training appears to be an important component for weight loss and, therefore, should be encouraged in obese patients with coronary heart disease because it produces favourable effects on lipid profile, glucose levels and blood pressure, as well as associated cardiovascular risk. 25,26 Another limitation is that angiographically visible collaterals represent only a fraction of the total collateral vessels as collaterals are angiographically demonstrable only when they reach 100 mm. However, this limitation influences the collateral score of both groups to the same extent and does not change the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 However, exercise training appears to be an important component for weight loss and, therefore, should be encouraged in obese patients with coronary heart disease because it produces favourable effects on lipid profile, glucose levels and blood pressure, as well as associated cardiovascular risk. 25,26 Another limitation is that angiographically visible collaterals represent only a fraction of the total collateral vessels as collaterals are angiographically demonstrable only when they reach 100 mm. However, this limitation influences the collateral score of both groups to the same extent and does not change the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Post hoc analyses of several studies revealed the benefits of this higher goal (Andersen et al, 1999;Jakicic et al, 1999;Jeffery, Wing, Thorson, & Burton, 1998). Similarly, participants in the National Weight Control Registry, who had lost at least 14 kg and kept it off for 1 year, reported that they expended approximately 2,800 kcal/week (Klem, Wing, McGuire, Seagle, & Hill, 1997).…”
Section: Group Behavioral Treatmentmentioning
confidence: 99%
“…The LEARN Program for Weight Management, 10 th Edition (Brownell, 2004) is popular with both clinicians and participants and is often employed in university-based clinics (Andersen et al, 1999;Foster et al, 2003;Womble et al, 2004). LEARN stands for lifestyle, exercise, attitudes, relationships, and nutrition.…”
Section: Treatment Protocols Learnmentioning
confidence: 99%